Management Challenges of Metastatic Spinal Cord Compression in Pregnancy - Davor Dasic; Narendra K. Rath; Mario Ganau; Zaid Sarsam (Case Reports in Surgery)
Primary and secondary spinal tumours with cord compression often represent a challenging condition for the patient and clinicians alike, even more so during pregnancy. The balance between safe delivery of a healthy baby and management of the mother’s disease bears many clinical, psychological, and ethical dilemmas. Pregnancy sets a conflict between the optimal surgical and oncological managements of the mother’s tumour and the well-being of her foetus. We followed the CARE guidelines from the EQUATOR Network to report an exemplificative case of a 39-year-old woman with a 10-year history of breast cancer, presenting in the second trimester of her first pregnancy with acute onset severe thoracic spinal instability, causing mechanical pain and weakness in lower limbs. Neuroradiological investigations revealed multilevel spinal deposits with a pathological T10 fracture responsible for spinal cord compression. The patient was adamant that she wanted a continuation of the pregnancy and her baby delivered. After discussion with her oncologist and obstetrician, we agreed to perform emergency spinal surgery—decompression and instrumented fixation. The literature search did not reveal a similar case of spinal metastatic breast cancer undergoing spinal instrumentation and delivery of a healthy baby a few months later. Following the delivery, the patient had further oncological treatment, including chemotherapy and radiotherapy. The paucity of such reports prompted us to present this case and highlight the relevance of a multidisciplinary approach involving obstetrician, oncologist, spinal surgeon, and radiologist to guide the optimal decision-making process.